PROTOTYPE DESIGN FOR TEXTILE INDUSTRY WASTEWATER TREATMENT - Azimah Salehah, Nur
Textile and textile product ranks the third position for national exports and provides 2.79 million employes. However, textile industry often contributes for the largest contamination in the Citarum River, especially the B3 pollutant. In this study, wastewater treatment plant is designed; it consists of five processes, namely equalization, pH neutralization, electrocoagulation, transition and filtration. Installation was tested with artificial waste from content of textile wastewater which is a solution of dye, high pH (NaOH) and starch. Measurement was conducted using pH sensor and turbidity sensor. pH neutralization process was conducted using solenoid valve with on-off system. Based on the simulation, the relationship between pH and neutralizer input for pH 9.1-10 was obtained. That is Y= 2 x 1013 x e-2.576x and Y= 4 x 1012 x e-2.336x for pH 10.1-11. The simulation test in pH neutralization plant is able to control pH wastewater to a regulated parameter from ministry of environment, which is 6 – 9. The electrocoagulation parameter is determined by time and energy consideration. The parameter was obtained using eight Al electrode that arranged in parallel, with 2 cm distance for every plate, DC power supply and pump flow rate 0.4 l/m. From the electrocoagulation test, the results were obtained that it’s proven to lower the turbidity until < 100 NTU . The test is conducted on the whole system delivers pH result 8.69 – 8.97 and the final result of turbidity is 23.64 NTU.